Job Satisfaction in the Structural Steel Detailing Industry, Philippines - Bicera, Richard Dela Cruz; LaMadrid, PhD, Richel L (ABAC ODI JOURNAL Vision. Action. Outcome, 2016)
Abstract Job satisfaction differs from one industry to another and more so from an individual to the other. Thus this study examined the level of job satisfaction of the management and operational employees along intrinsic, extrinsic and general job satisfaction areas in the Structural Steel Detailing Industry, Philippines. Specifically, this paper sought to determine 1) the significant differences on intrinsic, extrinsic and general job satisfaction when respondents are grouped along gender, age, educational attainment and tenure of work; and 2) the significant relationship between age, educational attainment, and tenure of work with job satisfaction. The latter proposed a hypothesized relationship stated as 1) the older or younger the employee, the higher or lower the job satisfaction, as the case may be; 2) the higher or the lower the educational attainment, the higher or lower the job satisfaction of the employee; and 3) the longer or the shorter the years of service to the company, the higher or the lower the job satisfaction of the employee. A survey of twenty (20) employees was conducted using the Minnesota Satisfaction Questionnaire (MSQ) – Short Form to measure job satisfaction. Results showed an average job satisfaction of the employees, which means that they perceive themselves to be satisfied with their job. Further, that neither significant differences nor relationship was found on intrinsic, extrinsic and general job satisfaction when the respondents were grouped along gender, age, educational attainment and tenure of work. Essentially, findings were discussed in relation to the existing literature on the influence of demographic variables on job satisfaction. Keywords: general job satisfaction, intrinsic, extrinsic, structural steel detailing